Gendered Populist Mobilization - KOUROU, NUR SİNEM (My University, 2019)
Populism has been stormed through the discussion and scope on political science. It has been discussed in many ways and associated with different issues. Even though the abundant of the literature, as many scholars mention, populism and gender have rarely considered (Spierings and Zaslove; 2017). One ofthe first studies has been emerged by Mudde and Kaltwasser (2015), but its conclusion discourages the researchers. The finding said that “the relationship between populism and gender is relatively weak but highly complex” (Mudde and Kaltwasser 2015: 36). This is important and also true because when populism declares itself in the antagonism between the people and the elite, the issue of gender is staying as an invisible topic. However, there is one crucial and certain outcome about the relationship between the populist parties and gender which is that the populist parties receive more male than female support (Spierings and Zaslove 2017; 822). However, there is a challenging situation in the case of Turkey where the percentage of female and male votes are even for JDP which a radical right populist party is also (KONDA; 2018). Therefore, this deviation frames the research question for this paper. This paper aims to answer how does populism mobilize the women in Turkey? I believe that empirical perspective provides a way out from complexity and uncertainty. Beyond the theoretical meaning of populism, I consider using the lens of populism to understand its mobilizational efforts within the society (Jansen; 2011). For this matter, the following questions will be answered to understand the mobilizational efforts of JDP in the level of female constituents. Firstly, “is there any populist organizational link between the JDP and female constituents? I will investigate the organizational structure of JDP women’s branches to answer the question. Secondly, “how is populism articulated as a mobilizational tool in the level of women’s branch?” For that, semi-structured and in-depth interviews will be conducted to analyze populist appeals in their links with the female. The third question is directly related to the relationship between the party and its women’s branches. I mean “how does the party mobilize women’s branches in terms of populist perspective? In a nutshell, the rising emanation of populism through political life has influenced various part of society. Even though women are ignored in political life, they have an active role in the case of Turkish populism for the JDP’s consolidation. Therefore, as an important part of the JDP, women’s branches will be unit of analysis of the research to represent the relationship between the populism and gender.